The Relationship between International Trade and Economic Growth - Putri Dewi Purnama; Ming Hung Yao (Jurnal Internasional Penelitian Bisnis Terapan, 2019)
The aim of this study is to find the relationship between international trade and economic growth in ASEAN countries. Three independent variables used to measure the economic growth include international trade, the exchange rate, and foreign direct investment. This study employs a pedroni panel cointegration test to examine the data from 2004 to 2015. The results show that there is a long term cointegrated relationship between international trade and economic growth in the ASEAN countries. International trade and foreign direct investment also have a long term, positive impact on economic growth. Meanwhile, the exchange rate also has a long term, negative influence on the economic growth. In addition, there is an indirect relationship and bidirectional causalities between the GDP and international trade, as well as between the GDP and the exchange rate. On the other hand, there is a direct relationship and a bidirectional causality between international trade and the exchange rate. The FDI leads GDP, international trade, and exchange rates. Our results suggest that international trade must be supported by government policies that aim to enhance the financing of new investment for economic growth.